Demand constraints and big government - L. Randall Wray (Levy Economics Institute of Bard College, 2007)
In a series of articles and books, Harold Vatter and John Walker attempted to make the case that the American economy suffers from chronically insufficient demand that leads to growth below capacity. Of particular interest are a 1989 Journal of Post Keynesian Economics article that extends Domar's work on the supply side effects of investment spending and a 1997 book that provides a comprehensive analysis of the evolution of the U.S. "mixed" economy. Their analysis of secular growth complements the well-known writings of Hyman Minsky, who also emphasized the role of the "big government" and the "big bank" in stabilizing an unstable economy over the cycle. This article will summarize, provide support for, and extend the Vatter and Walker approach, concluding with an examination of some of the dangers facing the U.S. economy today. As appropriate, the ideas of Minsky will be used to supplement the argument.
Keywords: E0; E6; F4; H6; 330; Demand Constraints; Economic Growth; Domar; Vatter and Walker; Sectoral Balances